Oral manifestations detected in COVID-19 patients: an integrative review (Research, Society and Development, 2021)
The aim of this integrative review consisted of verifying whether the oral manifestations detected in patients diagnosed with COVID-19 are useful in diagnosing the disease, whether they are a manifestation resulting from the disease, or whether there is evidence that there is no correlation between the pathologies. Therefore, articles in the PubMed, Lilacs, Scopus, Science Direct, Web of Science and Embase databases were searched, in addition to the search in gray literature. The terms used in the search were: “COVID-19” or “Sars-Cov-2” or “coronavirus” and “oral conditions” or “oral health” or “oral manifestations” and “diagnosis/complications” or “symptoms”. Thus, 1.305 articles were selected, of which 61 were selected to compose this review. Most of the included studies considered oral symptoms as taste changes, xerostomia and ulcerative lesions in the oral and labial mucosa. All symptoms related to this pathology still need further studies and investigations so that all mechanisms and manifestations related to it are completely elucidated.